The Effect Of Internal Marketing On Employee Commitment And Organisational Performance: The Role Of Management Support - Boateng, B. (University Of Ghana, 2021)
Internal marketing has been said to influence employee behaviour diversely; these include employee commitment to the organisation and performance. However, the dimensions of internal marketing are not commonly agreed upon and not much is known about the moderating influence of management support between employee commitment and organisational performance in small hotels, especially in sub-Saharan Africa. This study, therefore, attempts to determine internal marketing dimensions in the small hotel sector and evaluate its effects on employee commitment and organisational performance. The study also further examines the role of management support in the relationship between employee commitment and organisational performance. To achieve this, 300 respondents were selected using purposive and convenience sampling techniques, a structured questionnaire was used to collect data and AMOS software to analyse the data. The study established five dimensions of internal marketing compromising; internal communication, employee training and development, empowerment, and physical evidence. Together these internal marketing dimensions had twenty-two (22) items, employee commitment had seven (7) items, management support had five (5) items and the organisational performance had eight (8) items. The findings concluded that training and development was the internal marketing dimension impacting employee commitment, while empowerment did not have a significant impact on employee commitment. Physical evidence was found to have a significant positive effect on employee commitment and management support was also found to moderate the relationship between commitment and performance positively in the small hotels in Ghana.
MPhil. Marketing
Keywords: Employee Commitment; Organisational Performance; Internal Marketing